Optimizing the Parameters of Hot-wire CNC Machine to Enhance the Cutting of Plastic Foam - Mohammed, Israa Q.; Kadhum, Ali H. (Al-Khwarizmi Engineering Journal, 2019)
Hot-wire cutting is one of the important, non-traditional thermomechanical way to cut polymer, usually expanded foam and extruded foam, in low volume manufacturing. The study and analysis of Hot-Wire cutting parameters play an important role to enhance the quality and accuracy of the process and products. The effects on the surface have been investigated by using experimental tests designed according to the Taguchi orthogonal array (OA). In this study, four parameters with five levels for each parameter have been used: [temperature of wire (A) (100, 120, 130, 150, 160) °C], [diameter of wire (B) (0.3,0.4,0.5,0.7,0.8) mm], [velocity of cutting (C) (200, 300,400,500,600) mm/min], [and density of foam (D) (0.01,0.027,0.029,0.032,0.037) g/cm3]. Statistical software (MINITAB17) used to find the optimum conditions, which they are in Material Removal: 100 ˚C, 0.5 mm, 300mm/min, 0.032 g/cm3.